2018
DOI: 10.1002/pld3.48
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene causes transcriptomic changes in Synechocystis during phototaxis

Abstract: Ethylene is well known as a plant hormone, but its role in bacteria is poorly studied.We recently showed that Synechocystis sp. Strain PCC 6803 has a functional receptor for ethylene, ethylene response 1 (Etr1), that is involved in various processes such as phototaxis in response to directional light and biofilm formation. Here, we use RNA sequencing to examine the changes in gene transcripts caused by ethylene under phototaxis conditions. Over 500 gene transcripts across many functional categories, of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 69 publications
(188 reference statements)
2
20
0
Order By: Relevance
“…[51] In Synechocystis, these traits are controlled by type IV pili and extracellular polymeric substance (EPS). [52][53][54][55] Interestingly, ethylene affects the levels of pilin proteins and increases the number of type IV pili synthesized, and, alters the sugar composition of the EPS [42,56] suggesting that ethylene affects these physiological traits by changing type IV pili and EPS composition. Application of ethylene also causes a small increase in photosystem II levels with a parallel increase in growth rate of about 20%, [42,57] but these effects do not explain the much larger effects that ethylene has on the other physiological traits mentioned above.…”
Section: Synetr1 Is Functional Ethylene Receptormentioning
confidence: 99%
See 4 more Smart Citations
“…[51] In Synechocystis, these traits are controlled by type IV pili and extracellular polymeric substance (EPS). [52][53][54][55] Interestingly, ethylene affects the levels of pilin proteins and increases the number of type IV pili synthesized, and, alters the sugar composition of the EPS [42,56] suggesting that ethylene affects these physiological traits by changing type IV pili and EPS composition. Application of ethylene also causes a small increase in photosystem II levels with a parallel increase in growth rate of about 20%, [42,57] but these effects do not explain the much larger effects that ethylene has on the other physiological traits mentioned above.…”
Section: Synetr1 Is Functional Ethylene Receptormentioning
confidence: 99%
“…One showed that the fatty acid composition of the membranes was altered by ethylene [57] and another showed that application of ethylene to phototaxing cells caused wide-spread alterations in gene transcription causing altered mRNA levels for over 500 genes. [56] Additionally, ethylene causes a down regulation of several genes in the genomic region of SynEtr1 including CsiR1 (for Carbon stress inducted RNA1), slr1214, and slr1215. [56] These will be discussed more in the next section.…”
Section: Synetr1 Is Functional Ethylene Receptormentioning
confidence: 99%
See 3 more Smart Citations